Sulfur–Phenolate Exchange: SuFEx‐Derived Dynamic Covalent Reactions and Degradation of SuFEx Polymers. (29th July 2022) - Chao, Yang; Krishna, Akash; Subramaniam, Muthusamy; Liang, Dong‐Dong; Pujari, Sidharam P.; Sue, Andrew C.‐H.; Li, Guanna; Miloserdov, Fedor M.; Zuilhof, Han
Abstract: The products of the SuFEx reaction between sulfonimidoyl fluorides and phenols, sulfonimidates, are shown to display dynamic covalent chemistry with other phenols. This reaction was shown to be enantiospecific, finished in minutes at room temperature in high yields, and useful for both asymmetric synthesis and sustainable polymer production. Its wide scope further extends the usefulness of SuFEx and related click chemistries. Abstract : A sulfur(VI)–phenolate exchange (SuPhenEx) reaction between sulfonimidates and phenols has been shown to generate new sulfonimidates that undergo dynamic covalent reactions with other phenols. The fast, high‐yielding, and enantiospecific reactions are useful for both asymmetric synthesis and the degradation of SuFEx polymers. The wide scope of the reaction extends the usefulness of SuFEx and related click reactions.